Behavior and the Response of Cancer Cells on Anticancer Drug Treatment Monitored with Microelectrode Array. (2015) - Anh-Nguyen, T.; Tran, D.T.; Pliquett, U.; Urban, G.A.
Abstract: A cell-based impedance biosensor using microelectrode array has been developed for monitoring cellular activities of MCF-7 breast cancer cells and evaluating drug-induced apoptosis. Using this device, different activities of cells such as cell attachment, adhesion, and spreading are monitored by measuring impedance spectra and interpreting the data using an electrical equivalent circuit. In order to demonstrate pharmaceutical relevance, the cells were treated with 25 μM of anti-cancer drug Cisplatin. It was found that cell spreading caused a significant increase of impedance magnitude in the frequency range between 10 kHz and 100 kHz during 23 h of incubation, which is reversed after 24 h treatment with Cisplatin. This reversal is attributed to cell apoptosis, which is confirmed by microscopic observation of the cells.